Manajemen Implementasi Program Keluarga Berencana di Kecamatan Sungai Raya, Kabupaten Kubu Raya - Andri, Andri; Sirait, Tulus Borisman Evryan (JURNAL ADMINISTRASI KANTOR, 2024)
This study aims to analyze the management implementation of the Family Planning Program (KB) in Sungai Raya District, Kubu Raya Regency. The KB program is one of the government's efforts to control population growth and improve the quality of life of the community through birth control. This study uses a qualitative descriptive approach, with in-depth interview methods and direct observation of program implementers and participants in the field. The results of the study indicate that the implementation of the KB Program in Sungai Raya District has been running well, but there are still several obstacles, such as the lack of effective socialization and limited resources, including medical personnel and supporting facilities. However, public awareness of the importance of this program continues to increase, as seen from active participation in various activities related to KB. This study recommends increasing the capacity of implementing personnel and optimizing resources to ensure the continuation of the program and better target achievement in the future.   Keywords : Implementation, Public Policy, Family Planning.